“THEY MAY HAVE LIFE, AND HAVE IT ABUNDANTLY”: Mother Teresa and Her Critics - Saju Chackalacal (Journal of Dharma, 2012)
Perhaps it was a sheer coincidence: my reading of the book The Missionary Position: Mother Teresa in Theory and Practice by Christopher Hitchens (London & New York: Verso, 1995) and the life of Christopher Hitchens came to an end on the same day, to be exact on Thursday, 15 December 2011. While Mother Theresa was perceived to be instrumental in building up the lives of the least and the lost, Christopher Hitchens instrumentalized his life to pull down and destroy the life and associated public image of those personalities who were associated with the same downtrodden and the discarded in the mainstream society by employing his shrewd sophistry. It is quite strange to note that the fame of Hitchens came from the rhetorical flourish and verbal joust that he directed on the lives of those who had sacrificed their lives so that others may have life; to him the lives of great personalities such as Mother Teresa and Mahatma Gandhi belonged only to a “universe of the mediocre and the credulous.” Indeed, as he made his fame and, consequently, a living from his unhindered critique on Mother Theresa and others, she continued her unhindered service for those who were not cared for by anybody. While people of Hitchens’ status could relish on “promise and abundance and opportunity” available in an open and ever expanding world of self-realization and self-aggrandizement, the poor and the marginalized, the sick and the dying were only subjects for their intellectual snobbery and meticulously surgical but sterile scrutiny with complicated literary jargons; such intellectual and literary geniuses would argue for the enhancement of the quality of life of others, but would not move even their small finger to transform an iota in others’ lives. Any transformation in the quality of lives of the selfsame people, however, was made only by people of Mother Teresa’s commitment and availability.